Can we alter youth athlete's landing strategy in a stop-jump movement? - Mann, K. J.; O`Dwyer, N.; Bruton, M.; Edwards, S. (ISBS Proceedings Archive (Michigan), 2018)
The purpose of this study was to determine the effect of four different neuromuscular training programs on the kinematic landing patterns of pre-elite youth athletes during a stop-jump movement. Eighty-nine pre-elite youth athletes from the Western Region Academy of Sports Basketball, Netball, Softball, Triathlon and Field Hockey squads were recruited for biomechanical analysis before and after the completion of one of four randomly assigned 12-week training intervention programs, in conjunction with a strength and conditioning program. Results of this study identify youth athletes with poor movement competency acquire similar alterations in their kinematic landing pattern regardless of the type of training intervention completed, with no significant interaction identified between training groups, identifying that a basic strength and conditioning program can implemented to alter landing technique in a stop-jump task.